Efficient Modulation of Photonic Bandgap and Defect Modes in All‐Dielectric Photonic Crystals by Energetic Ion Beams. Issue 19 (14th July 2020) - Du, Guiqiang; Zhou, Xiachen; Pang, Chi; Zhang, Kaiyuan; Zhao, Yunpeng; Lu, Guang; Liu, Fen; Wu, Ailing; Akhmadaliev, Shavkat; Zhou, Shengqiang; Chen, Feng
Abstract: The photonic bandgap and localization in photonic crystals can be effectively modulated by energetic ion beams owing to the induced modification of the thickness and refractive indices of the materials. In this work, the modulation of photonic bandgap and defect modes in 1D all‐dielectric photonic crystals is investigated theoretically and experimentally by using carbon (C 5+ ) ion irradiation. It is found that the photonic bandgap and defect mode have a remarkable hypsochromic shift under the C 5+ ion irradiation. The degree of the blueshift mainly depends on the reduction of the material thickness that is nearly proportional to the fluences of C 5+ ions. The blueshift of the band edges and defect modes shows a step‐like behavior from transparency to opacification (near‐zero transmittance or high reflectance) or a converse trend. The work paves a new way to tailor the photonic crystals toward the development of novel devices with tunable specific wavelengths and wavebands. Abstract : The photonic bandgap and localization in photonic crystals are effectively modulated by using carbon (C 5+ ) ion irradiation owing to the induced modification of the thickness and refractive indices of the materials, where they have a remarkable hypsochromic shift. The work paves a new way to tailor photonic crystals toward the development of novel devices with tunable specific wavelengths and wavebands.